Potret Pendidikan Daerah Terpencil di Desa Sekamis Kecamatan Cermin Nan Gedang Kabupaten Sarolangun Provinsi Jambi - Faridl Hakim HAKIM; Anisa Nia Aprlia; Muhamad Aldi Al-Husaeni; Nike Siti Nurjanah; Rahmatang; Syahril (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Many complex issues affect education in rural areas. The purpose of this study was to determine the extent to which rural communities in Sekamis Village, Cermin Nan Gedang Village value education and identify the variables that contribute to the low level of education in the area. Case studies are used in the qualitative methodology of this study. Purposive sampling is used in the sampling method. In addition, descriptive analysis was used in data analysis. (1) The results of the study indicate that the residents of Sekamis Village, Kec Cermin Nan Gedang still have a very bad assessment of the value of education, which is indicated by the number of children who drop out of school. (2) The following factors contribute to the low educational attainment in Sekamis Village, Cermin Nan Gedang Village: Low awareness and understanding of the value of education due to obstacles related to the economy, environment, and travel time to school.